Long-term results of surgery for infantile esotropia - Makino, Shinji; Hozawa, Kozue; Sakai, Rieko; Kawasaki, Tomoko; Yamamoto, Hiroko; Kurosawa, Hiromi; Nishimura, Kayoko; Hanaoka, Reiko (JAPANESE ORTHOPTIC JOURNAL, 1999)
We evaluated the long-term results of surgery for infantile esotropia in 74 patients follow-up at least 4 years after surgery. Age on the initial visit ranged from 3 months to 6 years (mean=1.4 years), preoperative angle of esodeviation ranged from 25 prism diopters (PD) to 90PD (mean=53.4PD). Initial surgeries were performed ranged from 9 months to 13.5 years (mean=3.3 years). We examined ocular alignment preoperatively and 1, 6 months and 4 year postoperatively and final period. These patients were classified into five groups on the type of ocular alignment, i. e., A: orthophoria, B: residual esotropia≤10PD, C:≤20PD, D:>21PD, E: postoperative extropia. Final ocular alignment were 31 patients (53.5%) in Group A, 9 patients (15.5%) in Group B. The patients in Group A at 1 month postoperatively maintained orthophoria in 79.5% at 4 year, 61.6% at final period. On the other hand, postoperative extropia were 2.5% at 4 year, 20.6% at final period. We recommended that the target of ocular alignment should be undercorrection rather than appropriate correction and long-term management should be necessary while maintaining orthophoria with prisms glasses in daily life for infantile esotropia.